The cardio vascular simulator (CardioVASS) device on monitoring the physiology of blood flow circulation via angiographic image for medical trainee - Mohd Azrul Hisham, Mohd Adib; Khairul Shah, Affendy Yakof; Zulfikar, Anuar; Nizam, Abdullah; Idris, Mat Sahat; Nur Hazreen, Mohd Hasni (Akademi Baru, 2019)
The World Health Organization (WHO) reported the most killer disease throughout the world is cardiovascular disease. Every year, there are millions of deaths because of the catastrophic event of cardiovascular diseases. Therefore, it's crucial to understand the blood flow through the heart mechanism in the human body. In Malaysia, heart simulator normally used a conventional technique to run the procedure. The typical problem arises in carrying out the procedures was time-consuming as the medical educators need to handle for approximately 20 to 30 minutes. This lead to exhaustion both educators and students. The existing device in the market is not affordable and too expensive. Therefore, the objective of this study was to develop a new simulator for cardio that namely the Cardio Vascular Simulator (CardioVASS) device. The CardioVASS device is established for the learning and teaching process. The CardioVASS has three modes which are to study the physiology of blood circulation in the human heart, to observe the coronary artery disease mechanism and to understand the pathophysiological condition heart during catheter insert to the small arteries. This device also lightweight and portable so the cardiac training process can be conducted anytime during the learning session in class. This adequate to overcome long-term cardiovascular learning process. This device is also simple, easy to handle and more accurate because we used an automated control system.